INVESTIGATING THE IMPACT OF COVID-19 LOCKDOWN ON WORK-ATTRIBUTES OF PHARMACEUTICAL SALES REPRESENTATIVES THROUGH EXPLORATORY FACTOR ANALYSIS - Ehidiamen OAMEN, Theophilus (Journal of Healthcare Management and Administration (JHMA), 2022)
Factor analysis is a widely used quantitative technique in various disciplines, including the social, behavioral, and management sciences. It helps simplify complex data, reveal relationships among seemingly unrelated variables, and reduce data without losing essential information. While factor analysis has been extensively applied in many fields, its applications in social and administrative pharmacy research, particularly in pharmaceutical sales and marketing practice, have been largely untapped. This study aims to address this research gap and explore the use of factor analysis in the pharmaceutical sales and marketing industry, focusing on the effects of the COVID-19 pandemic on the work-attributes of pharmaceutical sales representatives (PSRs). Given the rapidly changing paradigm in the pharmaceutical industry due to the pandemic, understanding the impact on the roles and functions of healthcare supply chain staff, specifically PSRs, is crucial. By employing factor analysis, this study seeks to derive constructs that aid in the characterization, understanding, and prioritization of these work-attributes. The research utilizes exploratory factor analysis (EFA) on data obtained from a structured questionnaire administered to a pool of PSRs in Nigeria. The questionnaire assesses the perception of PSRs regarding the relevance of work-attributes during the COVID-19 lockdown.Two methods of factor extraction, namely Principal Component Analysis (PCA) and Principal Axis Factoring (PAF), are employed to analyze the data and compare the results from different analytical perspectives. The primary objective is to generate parsimonious elements of the constructs and gain insights into the impact of the pandemic on the work-attributes of PSRs. The findings of this study contribute to the existing literature on factor analysis and provide valuable insights for pharmaceutical sales and marketing practitioners, particularly in the context of the COVID-19 pandemic.